2022
DOI: 10.1038/s41467-021-27590-0
|View full text |Cite
|
Sign up to set email alerts
|

AI Pontryagin or how artificial neural networks learn to control dynamical systems

Abstract: The efficient control of complex dynamical systems has many applications in the natural and applied sciences. In most real-world control problems, both control energy and cost constraints play a significant role. Although such optimal control problems can be formulated within the framework of variational calculus, their solution for complex systems is often analytically and computationally intractable. To overcome this outstanding challenge, we present AI Pontryagin, a versatile control framework based on neur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 40 publications
(70 reference statements)
1
26
0
Order By: Relevance
“…Our study opens up several avenues for future research. One worthwhile direction for future work is to combine our methods with control theory (Chehrazi et al 2019;Xia et al 2021;Asikis et al 2022;Böttcher et al 2022a) to study how many new antibiotics are needed on average in a certain time interval (e.g., 10-20 years) to create a stable supply of effective treatment options and to keep the emergence of antibiotic resistance at a minimum. Another important direction is to estimate the minimum size of the proposed funding scheme for different regions to make antibiotic R&D viable under current and/or modified market conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Our study opens up several avenues for future research. One worthwhile direction for future work is to combine our methods with control theory (Chehrazi et al 2019;Xia et al 2021;Asikis et al 2022;Böttcher et al 2022a) to study how many new antibiotics are needed on average in a certain time interval (e.g., 10-20 years) to create a stable supply of effective treatment options and to keep the emergence of antibiotic resistance at a minimum. Another important direction is to estimate the minimum size of the proposed funding scheme for different regions to make antibiotic R&D viable under current and/or modified market conditions.…”
Section: Discussionmentioning
confidence: 99%
“…To summarize, RL-based optimization is preferable in scenarios where the interactions between agent and environment cannot be fully characterized mathematically. If one wishes to optimize actions for controlling a known dynamical system, it is more efficient to employ direct neuralnetwork-based optimizations (Asikis et al 2020, Böttcher et al 2022.…”
Section: Neural-network-based Optimization and Controlmentioning
confidence: 99%
“…For deterministic, continuous-time dynamical systems with real-valued control signals, control frameworks that are based on neural ordinary differential equations (ODEs) were introduced by Asikis et al (2020). In a related work by Böttcher et al (2022), it has been shown that such neural ODE control frameworks are able to automatically learn control trajectories that resemble those of optimal control methods. Another work by Asikis (2021) extends the aforementioned framework with real-valued control signals to discrete action spaces.…”
Section: Neural-network-based Optimization and Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we represent time-dependent control signals by artificial neural networks (ANNs) [29]. To parameterize and learn control functions, we use neural ordinary differential equations (neural ODEs) [30][31][32][33][34]. A schematic of the application of neural ODE control (NODEC) to a networked dynamical system is shown in figure 1.…”
Section: Introductionmentioning
confidence: 99%